(untitled) (Aporte Santiaguino, 2024)
The objective of this work was to determine the geomechanics of rocks and minerals in the province of Huari in the Ancash region, 2021, through rock engineering. It is a quantitative investigation. The application of geomechanics was carried out using the geological models, geomechanical model and numerical model through field work. The ISRM (Society International For Rock Mechanic’s) standard was used to characterize the rock mass. With the rock mechanics laboratory tests, the quality of the quartzite rock mass (tambillo) and hornfles (Cerro Saywa - San Marcos) was determined. The computerized program jordimoreno allowed the following results: the quality of the quartzite rock mass: RMR = 64 (basic) RMR = 54 (corrected) RMR = 59 (average) class III and subclass III-A (regular); The quality of the Horflens rock mass: RMR = 78 (basic) RMR = 78 (corrected) RMR = 78 (average) class II and subclass II-A (good). It is concluded that in these areas the mining and civil works guarantee the stability of the work to be carried out, with social and scientific contribution.